Street magic - Pierce, Tamora (New York : Scholastic Press, 2002)
Former "street rat" Briar Moss must face his past when he discovers a young mage in need of a mentor.
A novel.
Map on lining papers.
780
Accelerated Reader AR
Keywords: Fantasy; Magic -- Fiction; Fantasy